2021
DOI: 10.1055/a-1562-2521
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Risks, Complications, and Monitoring in Patients on Clozapine

Abstract: The Dutch Clozapine Collaboration Group is frequently asked for advice about the management of clozapine-treated patients when infected with or vaccinated against SARS-CoV-2. We provide state of the art information about the risks of SARS-CoV-2 infection for patients on clozapine and we give advice on measures to be taken, especially in regard to the monitoring of clozapine plasma levels, WBC count and differentiation during COVID-19 and after vaccination. We present an overview of relevant editorials, observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“… 18 In our systematic review, we found that a dangerous increase in clozapine blood levels is a common complication in critically ill COVID‐19 patients. 19 We also found that lymphocytopenia and granulocytopenia are generally mild and transient and a result of COVID‐19 rather than of clozapine treatment. Other complications of COVID‐19 associated with clozapine are delirium and COVID‐19 pneumonia.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“… 18 In our systematic review, we found that a dangerous increase in clozapine blood levels is a common complication in critically ill COVID‐19 patients. 19 We also found that lymphocytopenia and granulocytopenia are generally mild and transient and a result of COVID‐19 rather than of clozapine treatment. Other complications of COVID‐19 associated with clozapine are delirium and COVID‐19 pneumonia.…”
Section: Introductionmentioning
confidence: 53%
“…When after immunization a mild or moderate granulocytopenia is found—in contradiction with the European Medicines Evaluation Agency (EMEA) text—ongoing clozapine treatment with extra monitoring of WBC and granulocytes should be considered in long‐term recipients of clozapine. 19 A transient, not clinically significant, decline in lymphocytes and neutrophils is, after all, most likely caused by the vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 COVID-19 vaccination has been recommended for persons with SMI, including those on clozapine therapy. [1][2][3] SARS-CoV-2 infection can result in elevated clozapine levels and toxicity in clozapine users but limited information is available on risk of COVID-19 vaccinations in clozapine users. 2 Thompson et al reported a case of elevated clozapine levels presenting with delirium, increased falls and incontinence 4 days after receiving a dose of the BNT162b2 mRNA vaccine.…”
mentioning
confidence: 99%
“…[1][2][3] SARS-CoV-2 infection can result in elevated clozapine levels and toxicity in clozapine users but limited information is available on risk of COVID-19 vaccinations in clozapine users. 2 Thompson et al reported a case of elevated clozapine levels presenting with delirium, increased falls and incontinence 4 days after receiving a dose of the BNT162b2 mRNA vaccine. 4 Others have postulated that elevated clozapine levels and toxicity may be related to the inhibition of CYP1A2 enzyme during inflammation.…”
mentioning
confidence: 99%